Vision-Based System for Black Rubber Roller Surface Inspection - Thanh-Hung Nguyen; Huu-Long Nguyen; Ngoc-Tam Bui; Trung-Hieu Bui; Van-Ban Vu; Hoai-Nam Duong; Hong-Hai Hoang (Applied Sciences, 2023)
This paper proposes a machine vision system for the surface inspection of black rubber rollers in manufacturing processes. The system aims to enhance the surface quality of the rollers by detecting and classifying defects. A lighting system is installed to highlight surface defects. Two algorithms are proposed for defect detection: a traditional-based method and a deep learning-based method. The former is fast but limited to surface defect detection, while the latter is slower but capable of detecting and classifying defects. The accuracy of the algorithms is verified through experiments, with the traditional-based method achieving near-perfect accuracy of approximately 98% for defect detection, and the deep learning-based method achieving an accuracy of approximately 95.2% for defect detection and 96% for defect classification. The proposed machine vision system can significantly improve the surface inspection of black rubber rollers, thereby ensuring high-quality production.